A survey on critical factors and problems in implementing benchmarking towards achieving business competitiveness in SMEs - Baba Md Deros,; Sha’ri Mohd Yusof,; Azhari Md Salleh, (2006)
This paper is based on a survey conducted on top management of component suppliers to Malaysian automotive manufacturers. The survey was conducted to investigate the small and medium enterprises (SMEs) top managements’ perceptions on the following: critical competitive performance measures relative to their competitors; important goals that drive the SMEs to stay lean and competitive; on critical factors and major problems encountered in implementing benchmarking initiatives. This study aims at providing empirical evidence on the SMEs top managements’ perceptions of the above three major groups of factors. Analysis of the survey results showed that the three most critical competitive performance measures relative to competitors are product quality, manufacturing cost and technological competitiveness. Meanwhile, the three most important goals that help SMEs to stay lean and competitive are customer satisfaction, productivity improvement and operational performance. This survey also revealed the critical factors that must be in-place and major problems that must be overcome prior to the benchmarking implementation and adoption in order to ensure its success. The paper culminates with a discussion and general conclusion from the survey results